Correspondence of members of the 1st Southern Division regarding an incident in Tralee Bay involving the arrest of the sailing ship 'Seattle Spirit' by a British Destroyer, - Irish Republican Army. Southern Command, 1st (1922)
Includes copy letters from Dowdall and Co. Ltd and Moore & McCormack Co, Inc., New York, regarding SS "Kerhonkson" and ammunition found on SS "Seattle Spirit".